Visual Outcome after Intravitreal Avastin (Bevacizumab) for Persistent Diabetic Macular Edema - Haroon Tayyab, Uzma Hamza, Tehmina Jahangir, Samina Jahangir (Pakistan Journal of Ophthalmology, 2011)
Purpose: To determine the effect of intravitreal bevacizumab (Avastin) on visual acuity in patients with persistent diabetic macular edema. Material and Methods: A prospective, hospital based study conducted at Department of Ophthalmology, Jinnah Hospital Lahore from May 2010 to October 2010. Twenty eyes of 20 patients received a single intravitreal injection of Bevacizumab in a dose of 1.25mg / 0.05ml. The visual acuity was measured pre-injection and at 1, 4 and 12 weeks post-injection using Snellen’s visual acuity chart. Results: Prior to injection, there was 1 (5%) eye with best-corrected visual acuity (BCVA) better than or equal to 6/18, 10 eyes (50%) with VA between 6/24 and 6/60 and 9 (45%) with VA below 6/60. At 12 weeks post-injection, 2 (10%) eyes had BCVA better than or equal to 6/18; the number of eyes with BCVA between 6/24 and 6/60 were 12(60%), while 6(30%) eyes had BCVA below 6/60. The results are statistically significant (for each, p value is less than 0.05). Conclusion: This study revealed that intravitreal Bevacizumab (1.25mg/0.05ml) resulted in improvement of visual acuity in patients with persistent diffuse diabetic macular edema unresponsive to previous grid laser photocoagulation. The follow-up period was however too short to provide specific treatment recommendations, the short term results encourage further prospective studies with different treatment groups and longer follow-up.